Risk Factors for Complications following Introduction of Radical Surgery for Colon Cancer: A Consecutive Patient Series. (June 2019) - Furnes, B.; Storli, K. E.; Forsmo, H. M.; Karliczek, A.; Eide, G. E.; Pfeffer, F.
Background: Rectal cancer surgery is standardized, resulting in improved survival. Colon cancer has fallen behind and therefore more radical surgical techniques have been introduced. One technique is complete mesocolic excision. The aim of this article was to study the complications after the introduction of standardized complete mesocolic excision in a single center. Methods: Complete mesocolic excision was introduced in 2007, and data were collected from 286 patients prior to surgery (2007–2010). The surgeon decided on open or laparoscopic surgery. Follow-up information was recorded until 31 December 2015. Complications were classified according to a modified Clavien–Dindo classification. Results: Complications occurred in 47%, severe complications (grade III and IV) in 15%. In-hospital mortality was 3.5%. A total of 142 patients (49.7%) were operated by open surgery. Logistic regression revealed anemia (p = 0.001), open surgery (p < 0.001), and long operating time (p < 0.001) as significant factors for complications in general. Multinomial logistic regression revealed that severe complications occurred more often in males (odds ratio: 2.56; 95% confidence interval: 0.98–6.68), patients with anemia (odds ratio: 3.49; 95% confidence interval: 1.27–9.60), elevated body mass index (odds ratio: 1.14; 95% confidence interval: 1.02–1.28), and in open surgery (odds ratio: 9.95; 95% confidence interval: 2.58–38.35). Age was not associated with severe complications. Survival was not significantly influenced by complications. Overall survival (5 years) was 90% among patients with complications and 92% among those without complications. Conclusion: Severe complications following the introduction of complete mesocolic excision are patient dependent and related to open surgery. Patients selected for laparoscopy had less number of complications; therefore, introducing complete mesocolic excision by laparoscopy is justified. Identification of these factors can improve selection of appropriate surgical approach and postoperative patient safety.